Implementation of the Five Dimensions of the Capuchin Franciscan Formation in the Religious Development of Capuchin Youth in Sinaksak, Simalungun - Largus Nadeak (Abdimas Paspama, 2023)
The Capuchin Franciscan religious formation is an integral and continuous process that connects the charismatic, human, spiritual, intellectual, and missionary dimensions. In the practice of coaching, these five dimensions have not always been lived in a balanced manner so that some young religious still view formation as a structural and academic stage, not as a journey of self-transformation. This Community Service activity aims to strengthen the understanding, internalization, and implementation of the five dimensions of formation for Capuchin youth in Sinaksak, Simalungun. The activity was held on Saturday, June 10, 2023 at the Alverna Sinaksak Hall and was attended by 14 participants based on the official attendance list. The program uses a reflective, transformative, participatory, and contextual approach through interactive seminars, Focus Group Discussions, case studies, personal and communal meditations, and the preparation of action commitments. The validity of the implementation is verified through a letter of assignment, a signed attendance list, and a letter of thanks from partners. The results of the activity show the availability of structured coaching spaces, strengthening understanding of the five dimensions of formation, and commitment to integrate charisma, human maturity, spirituality, learning, and mission in community life. The sustainability of the program is directed through mentoring of formators, reflection journals, community evaluations, and commitment monitoring.